Effectiveness of Warehouse Receipt Management in Increasing Sharia Banking Access for Pepper Farming Communities - Ilyas, Rahmat; Iskandar, Iskandar (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
Pepper is one of the leading commodities in the plantation sub-sector and has great potential for Indonesia's economic growth. Indonesia is known as one of the world's main producers of pepper, especially black pepper which comes from Lampung Province and white pepper which comes from the Bangka Belitung Islands Province. Nationally, the Bangka Belitung Islands province is the province with the largest pepper income in Indonesia. Over time, efforts have emerged from the government to overcome the problem of fluctuating pepper prices resulting in low prices at the farmer level by implementing the Warehouse Receipt System (SRG). This research tries to examine how the management of pepper warehouse receipts in Bangka Belitung is related to WRS which is currently developing. The objects of this research are warehouse receipts. The results of this research indicate that the management of the Warehouse Receipt System in Bangka Belitung in general has not been implemented optimally, this can be seen from the public's lack of understanding about warehouse receipts, as well as the small number of pepper farming communities who use warehouse receipts as temporary storage, as for the obstacles faced by warehouse receipt managers, including the lack of information and outreach to pepper farmers about warehouse receipts themselves. Banking access for pepper farming communities in Bangka Belitung is quite good, because in its implementation sharia banks in Bangka Belitung can provide financing using warehouse receipts as collateral.